Strategic Learning Management through the Problem-Based Learning Model in Islamic Secondary Education - Elsa Nur Alfani; Riyuzen Praja Tuala; Nor Rochmatul Wachidah; Yetri Yetri (Al-Qalam Institue, 2026)
This study was motivated by the limited research on learning management in the implementation of the Problem-Based Learning (PBL) model, particularly at the madrasah level. It aimed to analyze the management of planning, implementation, and evaluation of PBL-based learning. The study employed a descriptive qualitative approach, with data collected through classroom observations, semi-structured interviews, and document analysis. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, and were validated through source and technique triangulation. The findings indicate that learning planning has integrated the syntax of the PBL model into instructional documents; however, its implementation has not been consistently carried out across all stages. Classroom management during group discussions requires improvement, particularly in role distribution and monitoring student participation. Although the evaluation process has addressed both learning processes and outcomes, it has not fully accommodated higher-order thinking skills indicators. This study implies that the effectiveness of PBL implementation is highly dependent on systematic and sustainable learning management practices.